Caracterização da Nappe Guaxupé na região de Nova Resende, faixa Brasília Meridional, Minas Gerais - Frederico Fava Zogheib (2016)
The Guaxupé terrain has been considered to be one of the thrust nappes developed in the southern Brasília belt (southeastern Brazil), during the Neoproterozoic Brasiliano orogeny. Two Brasiliano collisional events (ca. 794 Ma and ca. 630-610 Ma) formed a thin-skinned deformation, piled up structural system that makes up an ENE-plunging open syncline. This system comprises ortogneisses and paragneisses, showing increasing metamorphism towards west where high amphibolite to granulite facies (with charnockites) are found. We carried out a detailed structural analysis, as well as U-Pb (LA-ICP-MS) analysis on zircon and monazite from rocks of a lateral ramp of the Guaxupé nappe, showing transpressive deformation along a flank 80 km in lenght. Our data combined with compiled geothermobarometric data suggest an exhumation rate of 0.5 km/Ma for the Guaxupé nappe, starting between 15 km and 18 km deep in the crust, from ca. 615 Ma to ca. 575 Ma.